2021
DOI: 10.2174/1871520621666210126093630
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor Coactivator 5 is Correlated with Progression in Breast Carcinoma

Abstract: Background: Breast cancer (BC) is increasingly becoming the primary reason for death in women, which sounded the alarm. Thus, finding a novel management target for BC is imminent. Methods: The data of gene expression and clinicopathological characteristics were downloaded from The Cancer Genome Atlas (TCGA). The expression of nuclear receptor co-activator 5 (NCOA5) in 35 paired breast cancer and adjacent tissues were measured by quantitative real-time polymerase chain reaction (qRT-PCR). Univariate and Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As a regulator of IL-6, NCOA5 is thought to be related to inflammation. The expression of NCOA5 in breast cancer tissues was significantly higher than that in normal tissues, and the high expression of NCOA5 was associated with a decreased overall survival in breast cancer patients (Xia et al, 2021;Ye et al, 2017). Ye et al (2017) found that the high NCOA5 expression, old age (>60) and HER-2 expression were three independent high risk factors in luminal breast cancer.…”
Section: Ncoa5 and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…As a regulator of IL-6, NCOA5 is thought to be related to inflammation. The expression of NCOA5 in breast cancer tissues was significantly higher than that in normal tissues, and the high expression of NCOA5 was associated with a decreased overall survival in breast cancer patients (Xia et al, 2021;Ye et al, 2017). Ye et al (2017) found that the high NCOA5 expression, old age (>60) and HER-2 expression were three independent high risk factors in luminal breast cancer.…”
Section: Ncoa5 and Breast Cancermentioning
confidence: 99%
“…Ye et al (2017) found that the high NCOA5 expression, old age (>60) and HER-2 expression were three independent high risk factors in luminal breast cancer. Moreover, the high NCOA5 expression alone is also an independent risk factor in HER-2 positive breast cancer patients (Xia et al, 2021). Under the action of E2, NCOA5, as a co-activator of ERα, can be recruited to RORA promoter to promote the transcriptional activation of RORA (Sarachana and Hu, 2013).…”
Section: Ncoa5 and Breast Cancermentioning
confidence: 99%
“…Moreover, it has been verified that NCOA5 is highly expressed in breast cancer tissues, and is lowly expressed in adjacent non-cancerous tissues, and NCOA5 is highly associated with the poor prognosis of breast cancer patients ( 8 ). Furthermore, NCOA5 was greatly correlated with lymph node metastasis in breast cancer, and its expression could predict the overall survival time, thus NCOA5 is considered as a promising novel management target for breast cancer ( 9 ), whereas its specific regulatory mechanism in the progression of breast cancer has not been fully elucidated till now.…”
Section: Introductionmentioning
confidence: 99%